(untitled) (Proceedings of Southern Federal University. Philology, 2015)
Ovrutsky A.V. Keywords: cross-cultural space, literary and mass communication, Shazzo K. G., literary studies, interdisciplinary field. This article is devoted to the International conference "Cross-cultural space of literary and mass communication", which was held in October, 2014 in Maiсop. The conference was timed to the jubilee of Professor Shazzo K. G., a classical writer of Adygean literature. The author notes that this conference stood out with its interesting format and interdisciplinary field, which have become attractive and interesting for researchers in Russia, CIS and far abroad. The main topics of the reports were: the images of fiction and images of mass communication, as well as national and world literature.